NON-ADHERENCE TO ANTIHYPERTENSIVE TREATMENT IS A MAJOR DETERMINANT OF THE CLINIC-AMBULATORY BP DIFFERENCE IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2018) - Hamdidouche, I.; Pereira, H.; Gosse, P.; Bobrie, G.; Courand, P.-Y.; Delsart, P.; Mounier-Vehier, C.; Lantelme, P.; Denolle, T.; Dourmap, C.; Halimi, J.-M.; Girerd, X.; et al.
Abstract : Objective: Attended clinic SBP (cSBP) is usually higher than daytime ambulatory SBP in patients with resistant hypertension (RHTN), and the cSBP-dASBP difference is influenced by various factors. We investigated whether this difference was influenced by non-adherence to antihypertensive treatments (AHT) in a post-hoc analysis of the French Renal Denervation for Resistant Hypertension (DENERHTN) trial. Design and method: 86/106 patients with RHTN to 4 weeks of indapamide 1.5 mg/d, ramipril 10 mg/d (or irbesartan 300 mg/d), and amlodipine 10 mg/d confirmed by ABPM were included in this post-hoc study. Non-adherence was defined as the absence of at least one AHT by drug screening (LCMSMS and AcSDKP) in urine/plasma samples collected before ingestion of any AHT, ABP or cBP measurements. After the start of ABPM, patients were given their AHT and were asked to return to the study center the next morning without having taken their treatment to undergo cBP measurements. Results: 32/86 patients (37.2 %) were non-adherent to the triple therapy after 4 weeks. cSBP (171 ± 26 mmHg) was significantly greater than dASBP (158 ± 20 mmHg) in the non-adherent group (p < 0.0001) with a median cSBP-dASBP difference of 8.7 mmHg (IQR:3.5;22.3). In contrast, cSBP (150 ± 16 mmHg) did not significantly differ with dASBP (149 ± 13 mmHg) in the adherent group, with a median cSBP-dASBP difference of 1.5 mmHg (IQR:−7.0;9.0). The Bland–Altman plots showed a significant bias between cSBP and dASBP in the non-adherent group only. In univariate analysis, greater age, non-adherence to AHT and African origin were significant determinants of the cSBP-dASBP difference whereas BMI, gender, plasma creatinine were not. In the multivariate analysis, only age and non-adherence to AHT remained significantly related to the cSBP-dASBP difference. Conclusions: : Non-adherence to AHT impacts greatly the cSBP-dASBP difference in patients with RHTN.